2014
DOI: 10.1103/physrevb.90.134517
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected impact of magnetic disorder on multiband superconductivity

Abstract: We analyze how the magnetic disorder affects the properties of the two-band s± and s++ models, which are subject of hot discussions regarding iron-based superconductors and other multiband systems like MgB2. We show that there are several cases when the transition temperature Tc is not fully suppressed by magnetic impurities in contrast to the Abrikosov-Gor'kov theory, but a saturation of Tc takes place in the regime of strong disorder. These cases are: (1) the purely interband impurity scattering, (2) the uni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 41 publications
3
57
0
Order By: Relevance
“…28 and 29. We note that the effect of spin-magnetic impurities (not considered here microscopically) on the superconductive transition has been addressed recently in Ref. 32. Their results are consistent with our general symmetry analysis of section III, while our diagrammatic calculation of sections IV and V focuses on the other case of orbital-magnetic impurities and a possible microscopic mechanism for such impurities.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…28 and 29. We note that the effect of spin-magnetic impurities (not considered here microscopically) on the superconductive transition has been addressed recently in Ref. 32. Their results are consistent with our general symmetry analysis of section III, while our diagrammatic calculation of sections IV and V focuses on the other case of orbital-magnetic impurities and a possible microscopic mechanism for such impurities.…”
Section: Discussionsupporting
confidence: 79%
“…2(e), associated with a nontrivial phase factor, see Eq. (32), that is accounted for by the above vertex correction, this process enters only pairwise with its complex conjugate, and thus the resulting vertex corrections are real. Therefore, all physical observables which contain only electron self energies, Σ α , and vertex corrections, C α and C 0 α , are unaffected by the phase factor arising in the interband scattering process that is defined in Fig.…”
Section: A Self Energy and Cooperonsmentioning
confidence: 99%
“…The underlying reason is the multiband character of the Fermi surfaces in the FeBSs. In this case the order parameter may change sign due to impurities, as was demonstrated theoretically [26][27][28] and experimentally [29] with doping either to d-wave symmetry [30][31][32][33] or a change of sign [34]. Therefore, a universal tool to ascertain the pairing symmetry is much needed.…”
Section: Introductionmentioning
confidence: 99%
“…The s ± and s ++ states are expected to behave differently subject to the disorder [5,6,7,8,9,10,11,12,13]. In general, s ++ (s ± ) state should be stable (fragile) against a scattering on a nonmagnetic impurities [5,6,7].…”
mentioning
confidence: 99%
“…Detailed studies revealed that T c stays finite in the presence of nonmagnetic disorder in the following cases: i) s ++ state [8,9], ii) s ± → s ++ transition for the sizeable intraband attraction in the two-band s ± model in the strong-coupling T -matrix approximation [10] and via the numerical solutions of the Bogoliubov-de Gennes equations [14,15], iii) an unitary limit [16]. Magnetic impurities leave T c finite [13] in the case of 1) s ± superconductor with the purely interband impurity scattering, 2) s ++ state with the purely interband scattering due to the s ++ → s ± transition, and 3) the unitary limit for both s ++ and s ± states independent on the exact form of the impurity potential. But even if T c is suppressed, its behavior may differ from the AbrikosovGor'kov (AG) theory for the single-band superconductors [5], which states that T c is determined by the expression ln T c0 /T c = Ψ (1/2 + Γ/2πT c ) − Ψ (1/2), where Ψ (x) is the digamma function, Γ is the impurity scattering rate, and T c0 is the critical temperature in the absence of impurities [5].…”
mentioning
confidence: 99%